Exploring Surface-Driven Mechanisms for Low-Temperature Sintering of Nanoscale Copper - Jingyan Li; Zixian Song; Zhichao Liu; Xianli Xie; Penghui Guan; Yiying Zhu (Applied Sciences)
As the density of electronic packaging continues to rise, traditional soldering techniques encounter significant challenges, leading to copper–copper direct bonding as a new high-density connection method. The high melting point of copper presents difficulties for direct diffusion bonding under standard conditions, thus making low-temperature copper–copper bonding a focal point of research. In this study, we examine the sintering process at various temperatures by constructing models with multiple nanoparticles and sintering them under different conditions. Our findings indicate that 600 K is a crucial temperature for direct copper–copper sintering. Below this threshold, sintering predominantly depends on structural adjustments driven by residual stresses and particle contact. Conversely, at temperatures of 600 K and above, the activation of rapid surface atomic motion enables further structural adjustments between nanoparticles, leading to a marked decrease in porosity. Mechanical testing of the sintered samples corroborated the structural changes at different temperatures, demonstrating that the surface dynamic motion of atoms inherent in low-temperature sintering mechanisms significantly affects the mechanical properties of nanomaterials. These findings have important implications for developing high-performance materials that align with the evolving requirements of modern electronic devices.